CHARACTERISTICS OF ANALOG RICE OF SNAKEHEAD FISH CONCENTRATEWHICH FORTIFIED Chlorella sp. - Solo Oba Putra Sibagariang; Syahrul Syahrul; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the characteristics of analog rice of snakehead fish concentrate which fortified Chlorella sp. and to find out the best formulation. The method used in the research wasexperimental. The design used in this study was a Completely Randomized Design (CRD) of one factor, with 4 levels of treatment, namely the addition of Chlorella sp. as much as 0% (C1), 2% (C2), 4% (C3) and 6% (C4). The results showed that the four treatment levels significantly affected the appearance value, aroma, texture, ash content, fat, protein, carbohydrate, and fiber content but did not affect the texture value and moisture content. Treatment with an addition 2% of Chlorella sp. (C2) was the best treatment seen from organoleptic appearance, aroma, and taste. Meanwhile, treatment with addition 6% of Chlorella sp. (C4) was the best treatment seen from proximate tests such as ash (2.49%), fat (0.84%), protein (16.25%), carbohydrate (66.69%),and fiber content (0.97%). The average value of log transformation of total plate numbers in analog rice of snakehead fish concentrate fortified with Chlorella sp. shown that analog rice was still below the Indonesia National Standard threshold 1 x 106 colony/g.Keywords:analog ricecharacteristic, Chlorella sp., fish concentrate, fortified, snakehead fish